The Utilization of Pectin as Natural Coagulant-Aid in Congo Red Dye Removal - Felicia M K Haryanto; Andranyssa V M Rumondor; Hans Kristianto; Susiana Prasetyo; Asaf K Sugih (Journal of Multidisciplinary Applied Natural Science, 2024)
Coagulation using inorganic compounds such as aluminum sulfate is commonly used in water-wastewater treatment. However, there are some drawbacks to its utilization, such as a significant decrease in the treated water’s pH, non-biodegradable sludge, and a potential negative impact on human mental health (dementia and Alzheimer's). The use of inorganic coagulants can be minimized with the addition of natural-based coagulant-aid such as pectin. In this study, Congo red solution, a model dye substance, was coagulated by varying the pH (3–7) using alum coagulant to determine the best pH for coagulation. At the best pH, pectin was introduced at various doses (0–30 mg/L), and subsequently various dye concentrations (50–100 mg/L). The effect of pectin as coagulant-aid was compared with aluminum sulfate and pectin only; with a response of %removal and sludge volume. It was found that the Congo red dye coagulation had the best %removal at pH 6 indicating a charge neutralization mechanism. The addition of 15 mg/L pectin at an aluminum sulfate dose of 30 mg/L resulted in 97.7% dye removal with a sludge volume of 14 mL/L at a Congo red concentration of 50 mg/L. This value is higher compared to those of aluminum sulfate and pectin only which gave 75.6 and 3.19% removals, respectively. Furthermore, the addition of pectin as a natural coagulant-aid could halve the sludge volume due to the formation of denser flocs. The results show a promising potential of pectin as a natural coagulant-aid in water-wastewater treatment.